Evaluation of country infrastructure as an indirect measure of dog-mediated human rabies deaths - Bonaparte, Sarah C.; Moodie, Janae; Undurraga, Eduardo A.; Wallace, Ryan M. (Frontiers in Veterinary Science, 2023)
Background: Rabies is a neglected disease, primarily due to poor detection stemming from limited surveillance and diagnostic capabilities in most countries. As a result, there is limited ability to monitor and evaluate country, regional, and global progress towards the WHO goal of eliminating human rabies deaths by 2030. There is a need for a low-cost, readily reproducible method of estimating rabies burden and elimination capacity in endemic countries. Methods: Publicly available economic, environmental, political, social, public health, and One Health indicators were evaluated to identify variables with strong correlation to country-level rabies burden estimates. A novel index was developed to estimate infrastructural rabies elimination capacity and annual case-burden for dog-mediated rabies virus variant (DMRVV) endemic countries. Findings: Five country-level indicators with superior explanatory value represent the novel “STOP-R index:” 1) literacy rate, 2) infant mortality rate, 3) electricity access, 4) political stability, and 5) presence/severity of natural hazards. Based on the STOP-R Index, 40,111 (95% C.I. 25,854 – 74,344) global human rabies deaths are estimated to occur in 2022 among DMRVV-endemic countries and are projected to decrease to 32,349 (95% C.I. 21,110 – 57,019) in 2030. Interpretation: The STOP-R index offers a unique means of addressing the data gap and monitoring progress towards eliminating dog-mediated human rabies deaths. Results presented here suggest that factors external to rabies programs influence the successes of rabies elimination, and it is now possible to identify countries exceeding or lagging in expected rabies control and elimination progress based on country infrastructure.